METACOGNITIVE SKILL ON STUDENTS OF SCIENCE EDUCATION STUDY PROGRAM: EVALUATION FROM ANSWERING BIOLOGICAL QUESTIONS - Yasir, Mochammad; Fikriyah, Aida; Qomaria, Nur; Al Haq, Aushia Tanzih (University of Muhammadiyah Malang, 2020)
The metacognitive skill is a competency that must be mastered by students of educational program so that they are able to empower this competency in their students later. The purpose of this study was to analyze the metacognitive skill profile of students of the Science Education program at the University of Trunojoyo, Madura-Indonesia. The research involved 110 students as the research subject. Data were collected using metacognitive awareness inventory then analysed using descriptive quantitative method. The results indicated that students? metacognitive skill improved well (71.93%). Furthermore, the metacognitive skill in every component also enhanced well (64.53 - 75.81%), and the ?debugging strategies? in this skill developed excellently (88.30%). To sum up, the metacognitive skill on students of science education study program at University of Trunojoyo Madura enhanced well.